PERDAGANGAN INTERNASIONAL JASA TENAGA MEDIS MELALUI MUTUAL RECOGNITION ARRANGEMENT (MRA) DI KAWASAN ASEAN - Yemima Amelia Siagian; Jelly Leviza; Mahmul Siregar (Journal of USU International Law, 2017)
ABSTRACTThe effectuation of free flow of workforce in AEC (ASEAN Economic Community) has brought some impacts on the mobility of skilled workforce such as medical practitioners. International trade of service is then regulated in MRA (Mutual Recognition Arrangement) that has been approved in ASEAN countries’ regions. The research problems are how the legal aspect of MRA in the formulation of AEC (ASEAN Economic Community) is, how ASEAN agreement in the field of medical practitioners’ service is, and how the legal protection by ASEAN in the field of medical practitioners’ service is. The title of this research is “International Trade of Medical Practitioners via MRA (Mutual Recognition Arrangement) in ASEAN Regions”. Normative juridical research method is used in this research. The material or data are secondary legal materials. The data are collected through library study and analyzed by descriptive qualitative method. The legal aspect of MRA is that is acts as an agreement between two countries or more to reach an agreement which regulates each country’s interest of something. ASEAN Agreement in the field of medical practitioners’ service is made in Mutual Recognition Arrangement on Medical Practitioners, Mutual Recognition Arrangement on Dental Practitioner, and Mutual Recognition Arrangement on Nursing Services which has provided free entry for skilled medical practitioners to the other ASEAN countries stipulated in ASEAN MRA. The legal protection for the medical practitioners provided by ASEAN is also stipulated in Article 2, Article 5, and Article 6 of ASEAN MRA on Medical Practitioners through the receiving countries with good faith. Keywords: Medical Practitioners, MRA (Mutual Recognition Arrangement), ASEAN